2022
DOI: 10.1101/2022.02.16.22271078
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of bilateral sequential theta-burst stimulation on functional connectivity in treatment-resistant depression: first results

Abstract: Background: Previous studies suggest that transcranial magnetic stimulation exerts antidepressant effects by altering functional connectivity (FC). However, knowledge about this mechanism is still limited. Here, we aimed to investigate the effect of bilateral sequential theta-burst stimulation (TBS) on FC in treatment-resistant depression (TRD) in a sham-controlled longitudinal study. Methods: TRD patients (n = 20) underwent a three-week treatment of intermittent TBS of the left and continuous TBS of the right… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…A randomized sham-controlled study enrolling 60 treatment-refractory patients with recurrent major depressive disorder revealed that the mean antidepressant effect was highest in a combination of iTBS and cTBS (14). A threeweek treatment of iTBS over left DLPFC and cTBS of the right DLPFC (DLPFC) in patients with treatment-resistant depression (TRD) reported that significantly reduced functional connectivity between the left stimulation target and bilateral anterior insula (30). Third, our patient underwent accelerated iTBS over the left DLPFC with a 20 min interval, whereas the patients in the study by Philip et al received iTBS over the right DLPFC without interval.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized sham-controlled study enrolling 60 treatment-refractory patients with recurrent major depressive disorder revealed that the mean antidepressant effect was highest in a combination of iTBS and cTBS (14). A threeweek treatment of iTBS over left DLPFC and cTBS of the right DLPFC (DLPFC) in patients with treatment-resistant depression (TRD) reported that significantly reduced functional connectivity between the left stimulation target and bilateral anterior insula (30). Third, our patient underwent accelerated iTBS over the left DLPFC with a 20 min interval, whereas the patients in the study by Philip et al received iTBS over the right DLPFC without interval.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies suggest that the DLPFC and the right sgACC are functionally correlated during depressive episodes, and changes in their connectivity are associated with higher antidepressant efficacy for rTMS treatments [ 8 , 33 , 34 ]. Neither rTMS nor tDCS can reach the sgACC region directly, but a connectivity-based study by Fox and colleagues [ 8 ] showed that NIBS effects on the right sgACC depend on which specific location is targeted within the left DLPFC.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis was based on a subsample of patients from a longitudinal, clinical trial published previously [6]. Data of twelve TRD patients were included.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Targets were based on a previous study that indicated largest antidepressant effects and strongest negative functional connectivity with the subgenual cingulate cortex compared with other DLPFC locations [7]. MRI scans and clinical assessments were performed at baseline and after the last TBS session (for details, see [6]). TBS induced EF were simulated in anatomically realistic, volume conductor head models by the finite element method (FEM) using SimNIBS v3.2 [8].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%